The molecular diversity of transcriptional factor TfoX is a determinant in natural transformation in Glaesserella parasuis - Tang, Xiaoyu; Yang, Zhen; Dai, Ke; Liu, Geyan; Chang, Yung-Fu; Tang, Xinwei; Wang, Kang; Zhang, Yiwen; Hu, Bangdi; Cao, Sanjie; Huang, Xiaobo; Yan, Qigui; et al. (Frontiers in Microbiology, 2022)
Natural transformation is a mechanism by which a particular bacterial species takes up foreign DNA and integrates it into its genome. The swine pathogen Glaesserella parasuis (G. parasuis) is a naturally transformable bacterium. The regulation of competence, however, is not fully understood. In this study, the natural transformability of 99 strains was investigated. Only 44% of the strains were transformable under laboratory conditions. Through a high-resolution melting curve and phylogenetic analysis, we found that genetic differences in the core regulator of natural transformation, the tfoX gene, leads to two distinct natural transformation phenotypes. In the absence of the tfoX gene, the highly transformable strain SC1401 lost its natural transformability. In addition, when the SC1401 tfoX gene was replaced by the tfoX of SH0165, which has no natural transformability, competence was also lost. These results suggest that TfoX is a core regulator of natural transformation in G. parasuis, and that differences in tfoX can be used as a molecular indicator of natural transformability. Transcriptomic and proteomic analyses of the SC1401 wildtype strain, and a tfoX gene deletion strain showed that differential gene expression and protein synthesis is mainly centered on pathways related to glucose metabolism. The results suggest that tfoX may mediate natural transformation by regulating the metabolism of carbon sources. Our study provides evidence that tfoX plays an important role in the natural transformation of G. parasuis.